Chlorella pyrenoidosa Polysaccharide CPP-3a Promotes M1 Polarization of Macrophages via TLR4/2-MyD88-NF-κB/p38 MAPK Signaling Pathways - Yihua Pi; Qingxia Yuan; Shaoting Qin; Chundie Lan; Qingdong Nong; Chenxia Yun; Haibo Tang; Jing Leng; Jian Xiao; Longyan Zhao; Lifeng Zhang (Marine Drugs, 2025)
The immunomodulatory polysaccharide CPP-3a, purified from Chlorella pyrenoidosa, was investigated for its effects on RAW264.7 macrophages and underlying mechanisms, revealing that CPP-3a significantly enhanced phagocytic capacity and nitric oxide production while upregulating pro-inflammatory cytokines TNF-α and IL-6 and elevating the co-stimulatory molecule CD86, collectively driving robust M1 polarization. Mechanistically, TLR4-, TLR2-specific inhibitors, and TLR4-knockout cells confirmed TLR4 as the primary receptor for CPP-3a, with TLR2 playing a secondary role in cytokine modulation. CPP-3a activated NF-κB and p38 MAPK signaling pathways via the MyD88-dependent pathway, evidenced by phosphorylation of NF-κB/p65 with its nuclear translocation and increased phosphorylation of p38 MAPK, with these signaling activations further validated by specific pathway inhibitors that abolished M1 polarization phenotypes. Collectively, CPP-3a emerges as a potent TLR4-targeted immunomodulator with adjuvant potential for inflammatory and infectious diseases.